2021
DOI: 10.1111/jth.15250
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary embolism at autopsy in cancer patients

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 25 publications
0
26
0
1
Order By: Relevance
“…Previous studies have reported a 5-10% prevalence of pulmonary embolism in autopsied cancer patients. 57,58 Such deaths due to venous thromboembolism would have been misclassified as competing risk mortality instead of counting as a venous thromboembolic event, potentially leading to underestimation of incidence of venous thromboembolism.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Previous studies have reported a 5-10% prevalence of pulmonary embolism in autopsied cancer patients. 57,58 Such deaths due to venous thromboembolism would have been misclassified as competing risk mortality instead of counting as a venous thromboembolic event, potentially leading to underestimation of incidence of venous thromboembolism.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Reasons for these findings were unclear but could be postulated. Incidental VTE may not be thrombotic in nature as a recent large Dutch study showed a noticeable portion of PE (14.1%) observed at autopsy in cancer patients were tumor embolism, along with other types (septic, fat tissue, bone marrow) 43 . In addition, incidental VTE might already be subacute or chronic at the time of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Incidental VTE may not be thrombotic in nature as a recent large Dutch study showed a noticeable portion of PE (14.1%) observed at autopsy in cancer patients were tumor embolism, along with other types (septic, fat tissue, bone marrow). 43 11,19 Therefore, although incidental VTE may be associated with a lower rate of recurrent events, its prognostic role on overall mortality may be related to advanced or aggressive underlying malignancy 23 or poor performance status. 31 This study has limitations that are important to consider.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent autopsy study including almost 10,000 cancer patients, Gimbel et al reported a non-neglectable and stable over time proportion of cancer patients with PE using autopsies from 2008 (incidence = 11.7%, 95% CI (10.0–13.7)) to 2019 (incidence = 15.1%, 95% CI (11.9–18.7)) [ 33 ]. These data highlight that the diagnosis of PE in cancer patients remains extremely challenging and that the rate of fatal PE is severely underestimated [ 33 , 34 , 35 , 36 , 37 ]. The real rate of PE ranges from 10 to 35% and most likely depends on the type of cancer, with a higher risk in pancreatic, gynecological, lung, and biliary cancers [ 33 , 35 ].…”
Section: Epidemiologymentioning
confidence: 99%